Pengaruh Metode Pembelajaran Aktif Terhadap Motivasi dan Prestasi Belajar Siswa Disekolah - Rohayu, Lis; Muslimin, Muslimin; Ewisahrani, Ewisahrani (Infomatika: Pendidikan Informatika, 2025)
In the research conducted at this time has the aim to determine the effect of active learning methods on motivation and student achievement in school. This study uses the type or design of qualitative research in which the researcher must go down directly to observe what is being researched. The results of the analysis showed that there was a significant increase in motivation scores and student achievement in the experimental class compared to the control class. the average posttest value of students in the experimental class is higher than the control class with significant values. The discussion revealed that active involvement in the learning process makes students more motivated and understand the material better. In a full, active learning method, students are required to engage in their learning by thinking, discussing, investigating, and presenting. this can stimulate students in triggering the spirit of learning so that students are able to achieve their learning achievements at school. Active learning is very influential for students in their motivation and learning achievement.